Ginástica na escola: um estudo com professores de educação física em Miracema do Tocantins - Santos, Tháynna Soares dos (Universidade Federal do Tocantins, 2023)
The debate about body practices at school is not recent, such issues permeate until today, and the center of discussions almost always revolves around what should or should not be practiced in Physical Education (PE) classes. Currently, there is some agreement on the basic contents to be taught in the classroom by Physical Education professionals, which was built through many debates and discussions. According to Soares (1996, p. 11, emphasis in original), "modern Western Physical Education has taught GAME, GYMASTICS, FIGHTS, DANCE and SPORTS. We could say that these are the classical contents". This study focuses on gymnastics, understanding it and its expanded repertoire of possibilities as a specific content of PE that should, or at least should be developed/explored in the classroom. The study is theoretically based mainly on the work of Ayoub (2013), in his work "General gymnastics and school physical education", as well as studies by: Souza (1997), Soares (1992, 2004), Freitas and Frutuoso (2016), Silva and Sampaio (2012). To contribute to this debate, the study has as its main theme: gymnastics in school, it was proposed an investigation through the methodology of Focus Group (FG), with the teachers trained in PE and active (interested in participating in the research) in Miracema do Tocantins - TO, in the year 2019, in order to answer the following problem: is the content of gymnastics present in PE classes in schools in Miracema do Tocantins? Thus, it was possible to conclude with this study that gymnastics is an absent content in PE classes in the city and that this absence is justified mainly for two reasons: the rejection of students before the content (especially males) and the lack of knowledge on the part of PE professionals about the topic.